AIE Infinite Coordination Polymer for Phosphate Ion Detection via Aggregation State Modulation. Issue 37 (1st October 2020) - Yang, Yang; Dong, Jiaxuan; Li, Huihui; Guo, Dongyu; Yang, Weiting; Pan, Qinhe
Abstract: Coordination polymers (CPs) with aggregation‐induced emission (AIE) have been widely applied to fluorescent sensing based on the strategy of electron or energy transfer. Novel strategies still need to be explored to promote the application of AIE CPs in fluorescent sensing. Herein, an infinite coordination polymer (ICP), synthesized from Zn 2+, adenine and AIE ligand 4, 4'‐diphenic acid (DPA), was used to detect phosphate ion (Pi) via aggregation state modulation. The ICP was decomposed in the presence of Pi due to the coordination of Pi with Zn 2+, which disaggregated AIE ligand DPA along with fluorescence quenching. The ICP quantified Pi in the concentration range from 30 to 600 μM with a detection limit of 5 μM, which was much lower than the physiological level, and was applied to detecting Pi in urine with spiked recoveries in the range of 82.0–115.5 %. This work provides a novel strategy to design fluorescent probes with AIE CPs for the analytes exhibiting the decomposing ability, promoting the application of AIE CPs in fluorescent sensing. Abstract : In this work, an infinite coordination polymer, synthesized from Zn 2+, adenine and AIE ligand 4, 4'‐diphenic acid, was applied to detecting phosphate ion based on aggregation state modulation, that was to say, the coordination of phosphate ion with Zn 2+ caused the decomposition of the polymer and this disaggregated AIE ligand 4, 4'‐diphenic acid along with fluorescence quenching.